Elements of String Cosmology - Gasperini, Maurizio (Cambridge University Press, 2013)
The book is primarily intended for graduate students, not necessarily equipped with a background knowledge of cosmology and string theory; but any reader in possession of the basic notions of general relativity and quantum field theory should be able to benefit from the use of this book (or, at least, of a great part of it). Some chapters (in particular, Chapters 1, 7 and 8) could also be used as a “soft” introduction to modern cosmology for string theorists, while other chapters (in particular, Chapters 2 and 3) as a soft introduction to string theory for astrophysicists